Diseño de una guía metodológica de gerencia ágil para proyectos de investigación y desarrollo en áreas biológicas (2017)
This work stems from the need to carry out project management in Research and Development projects through a flexible management that takes into account the changing environments. Seeking to improve the processes of management and use of resources, objectives, time and budget. Three agile methodologies were selected: Scrum, Lean agile and Kanban, from which 13 tools and techniques were chosen that were applicable to Research and Development projects, to be used in the processes for project management. Was identify the need to strengthen all phases of the projects mangement as a result of the two population groups interviewed (leading researchers of CorpoGen projects as case of study, and leading researchers from external centers - national and international). Also, was determined that it was necessary to incorporate the project formulation phase, since a better definition of activities, schedule and budget from this phase facilitates the management processes, and that detailed planning can be done by short cycles, taking into account Its complexity and variation, using tools and techniques of agile methodologies. Also improve the processes of monitoring and control to optimize the execution and decision making in time, that allow to meet objectives, time and budget. With the characterization and tools selected, an interactive methodological guide was designed based on a combination of tools and techniques from agile management methodologies and traditional project management, which provides the required flexibility in handling the constant changes that are presented In the research environment, taking into account the management processes from start to finish and additionally considers strengthening the formulation of the project within the life cycle, seeking to optimize the subsequent management processes. It proposes values ​​and principles for its use, and a life cycle of Research and Development projects that includes four phases: Formulation, Plan-in, Agile execution containing iterative cycles (definition, action, reflection) and validation and Closing. It is aimed primarily at leading project researchers, but its use can be of great use to other members involved in managerial processes, such as administrative areas and managers or project managers. It includes descriptions, examples and suggestions for carrying out the activities, including some templates and formats that are proposed as a model to be adapted, adjusted and modified according to the particular needs of the project, the considerations and experience of researchers from other areas involved and Of the project manager, as well as organizational guidelines and guidelines. A guide validation process was carried out with leading researchers from CorpoGen's projects, external and an expert on agile methodologies, most of the recommendations were in a positive way.